Usability Testing on Android Application of Infrastructure and Facility Reporting Management Information System - Wicaksono, Satrio Agung; Firdausy, Danniar Reza; Saputra, Mochamad Chandra (Journal of Information Technology and Computer Science, 2018)
Decline in quality caused by daily use of facilities and infrastructure owned by an organization will certainly disrupt its function in supporting the performance of the organization. The solution that came from the research that has been conducted before is to develop android applications called Infiremis (Infrastructure and Facility Reporting Management Information System), that can be used to report damage to facilities and infrastructure and to track the status reporting. This android application was developed to be used by students, lecturers and staffs of Faculty of Computer Science Brawijaya University which those users has different background persona. Therefore, the usability of this android application need be tested to find out the value of effectiveness, efficiency and satisfaction of the application to fulfill its purpose. This research was conducted mainly to discover the result of usability testing towards the android application of infrastructure and facility reporting management information system. Based on Usability Testing that has been done show that the level of effectiveness and satisfaction of Infiremis respectively is 97,14% and 89,7%, whereas for the efficiency score is 89,9%.